The Perfect Government Development of the Governmental System of the United States of America - Kubinyi Márton (2000)
In my thesis paper I will analyse the development of the American governmental system, from the beginning to the point, where the government reached its present form laid down in the Constitution of the U.S. First the colonial times and authority of Great Britain, why it was unsatisfactory to the Englishmen of the colonies and how it led to the War of Independence. Then, a short overview of the war itself will follow with the most significant events, such as the creation of the Articles of Confederation. Next, I will point out the weaknesses of the governmental system it created and the reasons for its failure. Finally, I will give an analysis of the Constitution of the U.S. and the governmental system, which is described in it. I will point out the structural and fundamental changes compared to the Articles of Confederation, and list the facts why it is able to function and administer the United States of America.